A conceptual framework for minimising middle-income housing mismatch / Nor Atiqah Mustapa and Suhaila Ali - Mustapa, Nor Atiqah; Ali, Suhaila (Universiti Teknologi MARA, Perak, 2022)
The housing demand of the middle-income group cannot be ignored as they are the majority of the population in Malaysia which is about 40% out of the population. However, there is a mismatch between the supply and middle-income housing demand. The developer has always been eager to develop high-end products instead of affordable housing. This circumstance leads to the insufficient supply of middle-income housing. The mismatch is not only in terms of housing price, but also does not meet their housing preferences towards other housing attributes. Accordingly, this paper attempts to develop a conceptual framework for minimising middle-income housing mismatch. Thus, this paper reviewed the existing literature on the housing mismatch occurrences and the strategies to overcome this situation through government intervention. Almost all evidences from the studies indicate government, developer behaviour and buyer preferences have contributed to the middle-income housing mismatch occurrences. The findings were compiled through the creation of a conceptual model. Government intervention, developer behaviour and buyer preferences are included in the model as aspects that cause the housing mismatch occurrences. Significantly all these three aspects should interrelate with each other so that the potential of housing mismatch occurrences is low.